Israel, the UN, and the Question of the Authority of the UNTSO in the Demilitarized Zones Along the Border with Syria – 1949-1967 (IYUNIM: Multidisciplinary Studies in Israeli and Modern Jewish Society, 2026)
The armistice agreement signed between Israel and Syria following the war of independence gave the chairman of the Mixed Armistice Commission and the Chief of Staff of the United Nations Truce Supervision Organization [UNTSO] (UN officers) authorities to put civil lives throughout the demilitarized zones back on course. This clause was vaguely phrased and did not explain the nature of their authority. Over the years, many disputes erupted between the Israeli government and the UNTSO over the question of the interpretation of these authorities in civil issues in the Demilitarized Zone – draining the Hula Lake, evacuating Arab citizens, digging drainage channels, working agricultural lands, etc. Without any official interpretation, the chairmen and the Chiefs of Staff of the UNTSO interpreted these authorities according to their own understanding and judgment, interpretations that would often result in confrontations with the Israeli government and even reached discussions in the UN Security Council. However, according to the armistice agreement, Israel and Syria could call in the Armistice Commission in order to reach an agreed-upon interpretation, but the two never sought this option.            The following study is founded on archival resources and examines the Israeli government's fight against the broad interpretation of the UNTSO to their own authorities over the Demilitarized Zone. I will show that the Israeli government did not hesitate to take an aggressive stand against the UNTSO in order to weaken its power and authorities over the demilitarized zones and establish its own sovereignty over them, while UNTSO leaders tried to preserve and even increase their control, and would often and without hesitation pass the issue on to be discussed and resolved by the UN Security Council.
Keywords: UN; Armistice Agreement; Foreign Policy; the Observer Mechanism; Syria; Armistice; Demilitarized Zones